2022
DOI: 10.1167/tvst.11.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Contralateral Eye Comparison of Functional Optical Zone, and Visual Quality After SMILE and FS-LASIK for High Myopia

Abstract: Purpose To compare the functional optical zone (FOZ) and visual quality after small-incision lenticule extraction (SMILE) and femtosecond laser–assisted laser in situ keratomileusis (FS-LASIK) in correcting high myopia. Methods Ninety-two eyes of 46 high myopic patients with the same programmed optical zone (POZ) received SMILE in one eye and FS-LASIK in the contralateral eye. FOZ was calculated using a refractive power method. The decentration, visual outcomes, wavefro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…Correspondingly, previously reported data from this study and another prospective contralateral-eye study found no difference in total HOAs between eyes that underwent LASIK or SMILE. 4,23 Our findings with 12month postoperative data are also consistent with other prospective contralateral-eye studies comparing LASIK and SMILE, which reported no difference in quality of vision up to the postoperative 6-month visit. 9,23 The correlation observed between the severity of some visual symptoms and either residual refractive error or UDVA in the SMILE group was not observed in the LASIK group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Correspondingly, previously reported data from this study and another prospective contralateral-eye study found no difference in total HOAs between eyes that underwent LASIK or SMILE. 4,23 Our findings with 12month postoperative data are also consistent with other prospective contralateral-eye studies comparing LASIK and SMILE, which reported no difference in quality of vision up to the postoperative 6-month visit. 9,23 The correlation observed between the severity of some visual symptoms and either residual refractive error or UDVA in the SMILE group was not observed in the LASIK group.…”
Section: Discussionsupporting
confidence: 90%
“…4,23 Our findings with 12month postoperative data are also consistent with other prospective contralateral-eye studies comparing LASIK and SMILE, which reported no difference in quality of vision up to the postoperative 6-month visit. 9,23 The correlation observed between the severity of some visual symptoms and either residual refractive error or UDVA in the SMILE group was not observed in the LASIK group. The reason for the lack of an observed correlation in the LASIK group is likely because there was less variability in residual refractive error, and a greater proportion of eyes had better than 20/20 UDVA with LASIK.…”
Section: Discussionsupporting
confidence: 90%
“…1 C, 1 D). 14 , 15 The Pentacam scanned the anterior and posterior corneal surfaces by 360 degrees rotation within 2 second through a rotating Scheimpflug camera with a short wavelength slit-light, and 25 corneal Scheimpflug images, and a three-dimensional reconstruction of the cornea was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Centration on the Central 4-mm Area . The EOZ is defined as the outlined area with a difference of 0.5 D from the TCRP of a 4-mm area in the center of the cornea [38, 39]. The method adopted is as follows: in the TCRP map, taking the CV as the center, the EOZ is determined as the maximum ring diameter that is 0.5 D away from the TCRP in the central 4-mm area.…”
Section: Evaluation Of Eozmentioning
confidence: 99%